Abstract concepts in interaction: the need of others when guessing abstract concepts smooths dyadic motor interactions. Issue 7 (28th July 2021) - Fini, Chiara; Era, Vanessa; Da Rold, Federico; Candidi, Matteo; Borghi, Anna M.
Abstract : Abstract concepts (ACs, e.g. 'justice') are more complex compared with concrete concepts (CCs) (e.g. 'table'). Indeed, they do not possess a single object as a referent, they assemble quite heterogeneous members and they are more detached from exteroceptive and more grounded in interoceptive experience. Recent views have hypothesized that interpersonal communication is particularly crucial to acquire and use ACs. The current study investigates the reliance of ACs/CCs representation on interpersonal behaviour. We asked participants to perform a motor interaction task with two avatars who embodied two real confederates. Before and after the motor interaction task, the two confederates provided participants with hints in a concept guessing task associated with visual stimuli: one helped in guessing ACs and the other, CCs. A control study we performed both with the materials employed in the main experiment and with other materials, confirmed that associating verbal concepts with visual images was more difficult with ACs than with CCs. Consistently, the results of the main experiment showed that participants asked for more hints with ACs than CCs and were more synchronous when interacting with the avatar corresponding to the AC's confederate. The results highlight an important role of sociality in grounding ACs.